The security and deterrence policy of the Baltic states in 2014-2024 - Malużinas Martinas -. (2024)
The full-scale annexation of Crimea and Russia's invasion of Ukraine prompted the political elites of the Baltic states to devote even more attention to security problems and to update the defence plans of the Baltic region. The aim of the work is to analyze the development of the security and deterrence strategies of the Baltic states in the years 2014-2024 in the face of potential Russian threats on the border of the eastern flank of the North Atlantic Treaty Organization. The starting point for the discussion is the hypothesis that the sense of threat from the Russian Federation contributes to the intensification of trilateral military cooperation between Lithuania, Latvia and Estonia. The theoretical basis for the empirical analysis is the adaptive strategy model (so-called grand strategy ) developed by Colin Dueck .